Kawasaki disease epidemic: pitfalls - Romina Gallizzi; Giovanni Corsello; Giovanni Battista Pajno (Italian Journal of Pediatrics, 2020)
Abstract Recent reports have described in the pediatric population a new type of hyperinflammatory response manifested following contact with SARS-CoV-2, with some of the clinical features attributable to Kawasaki disease (KD). The purpose of this commentary is to remark on a possible recent association between SARS-CoV-2 and KD. Although today little is known about the etiology of KD, the most accepted hypothesis is that of a probable viral etiology, therefore, even the SARS-CoV-2 virus could trigger, in genetically predisposed subjects, an exaggerated inflammatory response that is clinically evident like the one described in KD.